2014
DOI: 10.1165/rcmb.2012-0525oc
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of the 5-Lipoxygenase Pathway in Lung Injury after Experimental Sepsis

Abstract: Postsepsis lung injury is a common clinical problem associated with significant morbidity and mortality. Leukotrienes (LTs) are important lipid mediators of infection and inflammation derived from the 5-lipoxygenase (5-LO) metabolism of arachidonate with the potential to contribute to lung damage after sepsis. To test the hypothesis that LTs are mediators of lung injury after sepsis, we assessed lung structure, inflammatory mediators, and mechanical changes after cecal ligation and puncture surgery in wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 44 publications
2
31
0
1
Order By: Relevance
“…In addition to 5‐LOX, the synthesis of bioactive LTs [LTB 4 and cysteinyl LTs (cysLTs, LTC 4 , LTD 4 , LTE 4 )] requires the enzymes LTA 4 hydrolase (LTA 4 H) and LTC 4 synthase (LTC 4 S). During injury, LT‐biosynthetic enzymes are induced, resulting in increased levels of both LTB 4 and cysLTs in damaged tissues such as the lung or skin . In addition to the COX and 5‐LOX pathways, AA can be metabolized by 12‐ or 15‐LOX enzymes, which are expressed by multiple cell types including myeloid cells and stromal cells.…”
Section: Biosynthesis Of Eicosanoids During Tissue Damage and Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to 5‐LOX, the synthesis of bioactive LTs [LTB 4 and cysteinyl LTs (cysLTs, LTC 4 , LTD 4 , LTE 4 )] requires the enzymes LTA 4 hydrolase (LTA 4 H) and LTC 4 synthase (LTC 4 S). During injury, LT‐biosynthetic enzymes are induced, resulting in increased levels of both LTB 4 and cysLTs in damaged tissues such as the lung or skin . In addition to the COX and 5‐LOX pathways, AA can be metabolized by 12‐ or 15‐LOX enzymes, which are expressed by multiple cell types including myeloid cells and stromal cells.…”
Section: Biosynthesis Of Eicosanoids During Tissue Damage and Repairmentioning
confidence: 99%
“…In particular, 5‐LOX deficiency or pharmacological targeting of the 5‐LOX pathway resulted in accelerated cutaneous healing, likely by reducing the production of reactive oxygen species (ROS) as well as of proinflammatory cytokines and chemokines in wounded skin . Similarly, 5‐LOX‐deficient mice and mice treated with LT‐modifying drugs were protected against acute inflammatory lung injury in a model of bacterial sepsis . However, these studies also suggested that in addition to the LTB 4 ‐BLT1 axis, cysteinyl LTs contributed to 5‐LOX‐driven inflammatory tissue damage and aberrant tissue repair.…”
Section: Roles Of Eicosanoids In Tissue Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…5-LO −/− mice or pharmacological inhibition of BLT1 actions protect mice during cecum ligation and puncture (CLP). 5-LO −/− and WT mice treated with a LT synthesis inhibitor have drastically lower levels of neutrophil infiltrates and lower levels of inflammatory cytokines such as IL-1β [84]. During CLP-induced sepsis, treatment with the BLT1 antagonist U-75302 decreases lung injury [85] as evidenced by decreased neutrophil recruitment.…”
Section: Aberrant Ltb4 Is Detrimental To Host Defensementioning
confidence: 99%
“…In other models of lung injury, antagonism of 5-LOX is protective; for example, pharmacological inhibition and gene knockout of 5-LOX protect against murine VILI,18 and in murine sepsis KO of the 5-LOX gene (or inhibition of the enzyme) provided more protection than use of leukotriene receptor antagonists (eg, Montelukast) 34. Antagonism of LTB4 is also effective in lung injury caused by haemorrhagic shock35 or in carrageenan-induced pleurisy 36…”
Section: Discussionmentioning
confidence: 99%